Republic of Estonia : Technical Assistance Report-Revenue Administration Gap Analysis Program-The Value-Added Tax Gap. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Technical Assistance Report discusses results of applying the Revenue Administration Gap Analysis Program Value-added Tax (VAT) gap estimation methodology to Estonia for 2007-2012. It highlights that between 2009 and 2012, VAT receipts failed to keep pace with nominal GDP and final consumption growth, owing to a growing compliance gap. Within the overall VAT compliance gap, the assessment gap in Estonia increased from 2009-2011, although the collections gap grew until 2009 and then decreased. The decrease of collections gap followed the introduction of automated management and sanctions of debt in 2010.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet